Menilai Kesiapan Organisasi terhadap Pembayaran Digital Berbasis Syariah: Studi Kualitatif pada Hotel Islam di Indonesia Regional - Nislah Khoirunnisa Nasution; Nurbaiti; Tuti Anggraini (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2026)
This study examines the organizational readiness of Hotel Syamsiah Sibuhuan, Padang Lawas, to adopt sharia-compliant digital payment amid the digital transformation of regional hospitality services. Although the hotel projects a sharia-oriented service identity, its digital transactions still rely on conventional banking channels. Using a qualitative case study design, data were collected through semi-structured interviews, field observation, open-ended questionnaires, and documentation involving the hotel owner, operational manager, finance staff, and front office staff. The findings show that the hotel is moderately ready for transition. Basic technological infrastructure is available, and staff demonstrate operational familiarity with digital transactions and a generally open attitude toward change. However, readiness is constrained by limited understanding of sharia-compliant payment principles, the absence of specialized training, the lack of formal standard operating procedures, and weak internal governance. The study argues that the main obstacle lies not in technological scarcity, but in the organizational misalignment between symbolic sharia identity, digital financial practice, and governance capacity